Importance of proper initial treatment of moderate and major burns - Vulović Dejan; Stepić Nenad (Vojnosanitetski Pregled)
Background/Aim. Burns are common injuries with frequency depending on human factors, development of protection, industry and traffic, eventual wars. Organized treatment of major burn injuries has tremendous medical, social and economic importance. The aim of this study was to analyze initial treatment of major and moderate burns, to compare it with the current recommendations and to signify the importance of organized management of burns. Methods. In a prospective study 547 adult patients with major burns were analyzed, covering a period of eight years, with the emphasis on the initial hospital admission and emergency care for burns greater than 10% of total body surface area (TBSA). Results. In the different groups of major burns, the percentage of hospital admission was: 81.5 in burns greater than 10% TBSA, 37.7 in burns of the functional areas, 54.5 in the III degree burns, 81.6 in electrical burns, 55.9 in chemical burns, 61.9 in inhalation injury, 41.0 in burns in patients with the greater risk and 100 in burns with a concomitant trauma. In the group of 145 patients with burns greater than 10% TBSA, intravenous fluids were given in 87 patients, analgesics in 45, corticosteroids in 29, antibiotics in 23 and oxygen administration in 14. In the same group, wound irrigation was done in 14.4%, removing of the clothing and shoes in 29.6%, elevation of the legs in 8.9% and prevention of hypothermia in 7.6% of the victims. There were no initial estimations of burn extent (percentage of a burn), notes about the patient and injury and tetanus immunizations. Conclusion. Based on these findings, it is concluded that there should be much more initial hospital admissions of major burns, and also, necessary steps in the emergency care of burns greater than 10% TBSA should be taken more frequently. On the other side, unnecessary or wrong steps should be avoided in the initial burn treatment.